Development of Arabic Interactive Learning Media Assisted by Kodular for Grade VIII at Islamic Junior High School - M. Tegar Wicaksana; Erlina (Language, Technology, and Social Media, 2023)
This study focuses on the development of an interactive Arabic language learning media, assisted by Kodular, for eighth-grade students at Madrasah Tsanawiyah (MTs). Arabic language learning presents challenges due to limited resources and student engagement, especially in the context of online learning. This study aimed to design and evaluate the feasibility, effectiveness, and student responses to this interactive learning media, which was developed using the 4D model: Definition, Design, Development, and Dissemination. The media was validated by experts in both media and content, receiving high ratings of 98%, categorizing it as highly suitable for educational purposes. The study employed a quasi-experimental design, with pre-test and post-test assessments conducted at two schools: MTs Guppi 2 Tanjung Karang and MTs NU Tanjung Karang, involving 40 students in total. Data were collected through questionnaires, interviews, tests, and documentation. The results from the t-test analysis showed statistically significant improvements in student learning outcomes. At MTs Guppi 2, the t-value was 12.55 (p < 0.05), and at MTs NU, it was 10.38 (p < 0.05), indicating the effectiveness of the Kodular-assisted media in enhancing student engagement and academic performance. The study concludes that the Kodular-based interactive learning media is a highly effective tool for improving Arabic language proficiency in eighth-grade students. Its advantages include accessibility without the need for internet connectivity, offering a flexible and engaging learning experience. The findings suggest that integrating mobile-based learning tools can significantly address the challenges of traditional learning environments, especially in regions with limited internet access. Furthermore, this research underscores the potential of Kodular as a platform for creating educational media, providing a low-cost, accessible solution for educators in diverse settings.